Correction: Penetrating probability and cross section of the Li+–C60 encapsulation process through an ab initio molecular dynamics investigation. Issue 41 (11th October 2018) - Ho, Thi H.; Kawazoe, Yoshiyuki; Le, Hung M.
Abstract : Correction for 'Penetrating probability and cross section of the Li + –C60 encapsulation process through an ab initio molecular dynamics investigation' by Thi H. Ho et al., Phys. Chem. Chem. Phys., 2018, 20, 7007–7013.